Persepsi Kesiapan, Sikap dan Motivasi Belajar Mandiri terhadap Pembelajaran Matematika secara Kolaboratif Berbasis Online - Lino, Nopa Sampe; Ilyas, Muhammad; Sehe, Sehe (Universitas Cokroaminoto Palopo, 2024)
The research aims to describe the readiness, attitude and motivation of self-learning towards collaborative online based mathematics learning during the covid-19 pandemic. The researcher applies a quantitative descriptive methods in this study. Data collection has been done by giving three kinds of questionnaires including readiness, attitude and self learning motivation during covid-19 pandemic, and has distributed to 80 students in 3 Senior High School and 1 Vacational High School at Nuha district. The result of this research shows that the students are ready for Mathematics learning collaborative online based during covid-19 pandemic. That is supported by their ability to operate the computer and the usage of internet as well as their online learning experience they have been through for 2 years in online learning situation. Students' motivation towards learning mathematics through the implementation of online based collaborative learning is inconsistent even though it is in moderate level of motivation. Some students prefer the face to face learning process to online learning process and think that the previous learning will provide better learning outcomes. This is a challenge for teachers to prepare for the new normal phase with more interesting teaching material, strategies and learning methods by the development of digitalization of learning